Pengaruh Budaya Organisasi Dan Stres Kerja Terhadap Kinerja Karyawan PT X: The Influence of Organizational Culture and Work Stress on Employee Performance at PT X - Nabila Cita Suci; Murniyati Murniyati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
In an increasingly competitive business environment, organizational culture has become an important factor influencing employee attitudes and behavior, including at PT X as a mining contractor. In addition, work stress resulting from task pressure and the work environment can also affect performance. This study aims to examine the influence of organizational culture and work stress on the performance of PT X employees, which has not been specifically researched before. This study employs a quantitative causal approach with 50 respondents as the sample. Data were collected via an online questionnaire and analyzed statistically to determine the influence of the two independent variables on performance, both partially and simultaneously. The determination coefficient test results indicate that organizational culture and work- related stress together influence performance by 45.8%. The t-test indicates that organizational culture has a significant partial effect (calculated t = 5.891 > table t = 2.011; sig. 0.000 < 0.05), while work stress does not (calculated t = 0.442 < table t; sig. 0.660 > 0.05). The F test shows that both simultaneously have a significant effect (F calculated 19.824 > F table 3.20; sig. 0.000 < 0.05).